Рабы, рабовладение и роль рабства в Угарите XIV-XII вв. - Гельцер, M. Л.
Heltzer, M. L.; Slaves, Slave-owning and the Role of Slavery in Ugarit in the Fourteenth and Thirteenth Centuries B.C.; engl. Résumé.